EMOTIONAL AND EVALUATIVE COMPONENTS OF COMPARATIVE PHRASEOLOGICAL UNITS - Israilova Manzura Jamolovna (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the evaluative and emotional components of the connotative meaning of comparative french phraseological units are analyzed not separately, but simultaneously, because they are interrelated. It is in the evaluations that the corresponding feelings realized in a certain situation are hidden. In other words, at the linguistic level, it is easier to distinguish a semantic evaluation than an emotional component that unfolds in context.